Գրականագիտական լուրջ ներդրում - Աթայան, Անահիտ
В статье обсуждается книга С.Ханяна «Поэзия А. Арутюняна» как результат многолетнего труда автора. Аналитико-методические исследования, оценивая сборники А. Арутюняна, раскрывают тот факт, что автор хорошо освоил лучшие традиции мировой литературы. Работа С.Ханяна - это и зрелое исследование, и очевидный вклад в современную армянскую литературу, первый фундаментальный обобщающий труд в области арутюноведчества. In the article ―"A significant literary contribution" the book ―The poetry of A. Harutyunian‖ by S. Khanian is discussed. The collections of A. Harutyunian are evaluated through analytical and methodological investigations, revealing the fact that the author had mastered the best traditions of the world literature. The work of S. Khanian is both a mature research and an obvious contribution to the modern Armenian literature, the first fundamentally generalizing work made in the field of study of Harutyunian‘s works.
Keywords: Գրականագիտություն